ASPEK HUKUM DALAM IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH TERHADAP PELAYANAN PUBLIK DI ERA DIGITAL - Sutrisno, Hafiz (Jurnal Pahlawan, 2024)
Digitalization of government services, such as e-government and digital-based applications, aims to provide convenience for the public in accessing administrative services, licensing, and various other public services. However, the implementation of local government policies in public services in the digital era still faces various challenges, both from legal and technical aspects. This study uses a normative legal method with a statute approach and a conceptual approach. Although regulations are available, many local governments still experience obstacles in their implementation. Due to the lack of harmonization between central and regional regulations, weak digital infrastructure, and limited human resource competency in managing digital systems and cybersecurity issues. Keywords: Public Service, Digital Era